Environmental Management Accounting in a Manufacturing Arm of a Financial Services Sector Organization - A Case of a Sri Lankan Organization - Edirisooriya, K.K.; Noopehewa, P.U.; Perera, S.A.D.C.U. (My University, 2014)
Purpose - The purpose of this paper is to examine why and to what extent a manufacturing arm of a financial sector organization in Sri Lanka adopts and implements environmental Management Accounting practices. Design/methodology/approach - The study followed a case study approach. The primary data were collected by conducting semi structured interviews and observing organizational processes. Secondary data were collected through analyzing documents such as internal records, online sources including the organization’s web site and various other records. In the data collection process higher emphasis was placed on data triangulation. Data analysis was carried out following an explanation building approach. Findings - The study identified that although the waste management initiatives are practiced to a great extent, they do not encompass a comprehensive and an integrated approach. The intention for cost savings and the significance of the output being generated are the main drivers for adopting environmental management accounting practices. Top management awareness remains poor and an integrated strategic approach for sustainability management is not well established within the organization. Research limitations/implications - Due to the context specific characteristics, the findings of the study will be difficult to generalize. Also, the study mainly emphasized on the process of collecting and re-using gold dust, but other critical areas such as waste water and air pollution was not investigated. Originality/value - The study attempts to fill the gap of environmental management accounting research in a manufacturing operation of financial sector of a developing country. The findings of the study will be expedient to the sector in developing and retaining environmental management accounting practices.
Keywords: Developing country; environmental management accounting; financial service sector; waste management initiatives.